Safety evaluation of ethanol extract from Artocarpus altilis leaves as a herbal medicine candidate: Studies in acute and subchronic toxicity - Fitrya Fitrya; Elfita Elfita; Ferlinahayati; Salma Fayzah Septami; Umi Tsalsa Sabrina; Fatma Sri Wahyuni; Annisa Amriani; Rennie Puspa Novita (Phytomedicine Plus)
Background: Artocarpus altilis is a traditional medicine proven to be efficacious in several pharmacological tests using animal models. However, there have been no reports regarding its safety so far. Therefore, this study aimed to evaluate the toxicity of ethanol extract of A. altilis (EAA) in experimental animals. Methods: An acute toxicity test was carried out based on OECD 423 guidelines with a single dose of 10,000 mg/kg BW. Subchronic toxicity was tested for 28 days based on OECD 407 guidelines, with 200 and 400 mg/kg BW doses. Mortality, variations in body weight, hematological and biochemical markers, organ index, and the histology of vital organs were all used to study toxic symptoms. Results: The results showed that the ethanol extract of A. altilis leaves was practically nontoxic with an LD50 value greater than 10,000 mg/kg. A subchronic toxicity study showed that the extract did not cause death or weight loss in rats and had no toxic effects on hematology or serum biochemistry. However, the subchronic toxicity study at a dose of 400 mg/kg BW revealed changes in the liver index and histology, although these did not affect the biochemical parameters of the organ. Conclusion: The LD50 value of the extract was greater than 10,000 mg/kg BW. The ethanol extract of A. altilis leaves at a≤ 400 mg/kg dose showed no toxicity in the subchronic phase. The results of this study support the safety of using EAA as a herbal medicine candidate.